2021
DOI: 10.1055/s-0041-1731717
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocyte Cytoskeletal Proteins in Platelet Biogenesis and Diseases

Abstract: Thrombopoiesis governs the formation of blood platelets in bone marrow by converting megakaryocytes into long, branched proplatelets on which individual platelets are assembled. The megakaryocyte cytoskeleton responds to multiple microenvironmental cues, including chemical and mechanical stimuli, sustaining the platelet shedding. During the megakaryocyte's life cycle, cytoskeletal networks organize cell shape and content, connect them physically and biochemically to the bone marrow vascular niche, and enable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 167 publications
0
7
0
Order By: Relevance
“…For the production of platelets MKs undergo a series of remodeling events that result in thousands of platelets being released from a single cell [76]. All the proteins found to be interact with THPO protein are known to regulate the platelet formation and functions [77][78][79]. The interaction of THPO protein with other proteins suggested that there might be potential alternate mechanisms that could affect platelet production, morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…For the production of platelets MKs undergo a series of remodeling events that result in thousands of platelets being released from a single cell [76]. All the proteins found to be interact with THPO protein are known to regulate the platelet formation and functions [77][78][79]. The interaction of THPO protein with other proteins suggested that there might be potential alternate mechanisms that could affect platelet production, morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…activation of platelets, accompanied by endothelial damage, subsequent fibrin deposition and the formation of thrombosis 21 . In Lemierre's syndrome direct evidence of pus collections surrounding the internal jugular vein as well as pus within the thrombi have been described 22 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Actin-binding protein. Suggested to be a negative regulator of megakaryocyte platelet production, meaning high levels could cause thrombocytopenia 20,21 .…”
Section: Plastin-2mentioning
confidence: 99%
“…Although WASP is involved in all main stages of megakaryocyte (MK) maturation—invaginated membrane system (IMS) formation, podosome formation, migration and proplatelet release, 13 the MKs in WAS patients remain largely unexamined.…”
Section: Introductionmentioning
confidence: 99%
“…an increased tendency to undergo programmed cell death, which in case of platelets results in a shortened lifespan and accelerated clearance. 12 Although WASP is involved in all main stages of megakaryocyte (MK) maturation-invaginated membrane system (IMS) formation, podosome formation, migration and proplatelet release, 13 the MKs in WAS patients remain largely unexamined.…”
mentioning
confidence: 99%